The blockchain internet of things: review, opportunities, challenges, and recommendations - Mahmood A. Al-Shareeda; Murtaja Ali Saare; Selvakumar Manickam (Indonesian Journal of Electrical Engineering and Computer Science, 2023)
A new technology known as the internet of things (IoT) allows both physical and virtual items to be linked and communicated with one another, creating new digital services that enhance our fineness of sustenance. The IoT system has a number of benefits, but because of its present centralized architecture, there are several problems with regard to data integrity, security, privacy, and single points of failure. The future development of IoT applications is hampered by these difficulties. To tackle these problems, it might be best to integrate the Internet of Things with one of the distributed ledger solutions. The blockchain is one of the most frequent and well-liked varieties of distributed ledger technologies. Numerous advantages can result from integrating blockchain technology with the IoT called blockchain internet of things (BIoT). In this paper, we show a brief overview of blockchain, its components of blockchain, and its features of blockchain. Meanwhile, we describe the architecture of BIoT, Issues of BIoT, and BIoT applications. Additionally, this paper provides a future research challenge and open issues.